Beyond the Tyranny of Contemporary Architecture / Wanderings of an Architect-Composer in the Real World - Alexiou Takis Prof. Dr. (Four Seasons, 2004)
A critical view of the life and reality, which we all share and live in nowadays. Prologue, ''Where is One's Conscience'', ''Clever'' Bombs and ''Clever'' Homes, The City of Speed - The City of Destruction, The Architecture of the Confused, The Dance of the ''Right Angle'' is Continued, Architectural Education Today and Tomorrow, The Four Journeys of a New Architecture, Forms and Colors, Interview for a Humane Architecture, Suggested Bibliography, Brief Curriculum Vitae, Appendix - Greek Translation.